2017
DOI: 10.1111/jace.14786
|View full text |Cite
|
Sign up to set email alerts
|

Thermal properties of simulated Hanford waste glasses

Abstract: The Hanford Tank Waste Treatment and Immobilization Plant will vitrify the mixed hazardous wastes generated from 45 years of plutonium production at the Hanford Site in Washington State. The molten glasses will be poured into stainless steel containers or canisters and subsequently cooled for storage and disposal. For appropriate facility design and operations to handle such highly energy‐consuming processes, knowledge of the material properties is required. The thermal properties (heat capacity, thermal diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 25 publications
4
14
0
Order By: Relevance
“…This is an increase of ~11% for a 1.18 mass% increase in measured SO 3 in the bulk glass. These values were similar to previous values reported for waste glasses . The rate of increase in thermal diffusivity decreases with increasing SO 3 additions, becoming somewhat invariant in the three glasses that exceeded the sulfur solubility (>2.0 mass% SO 3 additions).…”
Section: Resultssupporting
confidence: 89%
See 4 more Smart Citations
“…This is an increase of ~11% for a 1.18 mass% increase in measured SO 3 in the bulk glass. These values were similar to previous values reported for waste glasses . The rate of increase in thermal diffusivity decreases with increasing SO 3 additions, becoming somewhat invariant in the three glasses that exceeded the sulfur solubility (>2.0 mass% SO 3 additions).…”
Section: Resultssupporting
confidence: 89%
“…All samples exhibited a ~25% increase in heat capacity with a 375°C increase in temperature. This was consistent with the literature and also indicated that the temperature range of measurement was below the Debye temperature . At the Debye temperature, all phonon modes would be active, and the relative heat capacity increase with temperature would drastically reduce.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations